Europarl: Swedish-Greek - Språkbanken Text (University of Gothenburg, 2024)
Part of European Parliament Proceedings Parallel Corpus

Del av European Parliament Proceedings Parallel Corpus
Europarl: svenska-grekiska
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik